1998
DOI: 10.1002/(sici)1521-4028(199803)38:1<9::aid-jobm9>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alginate-encapsulated Azotobacter chroococcum as a phage-resistant and an effective inoculum

Abstract: The efficiency of free and alginate-encapsulated Azotobacter chroococcum in fixing nitrogen and their susceptibility to bacteriophages were studied in pure liquid cultures (in vitro) and under cultivated soil conditions (in vivo). Bacteriophages of A. chroococcum were isolated and were found to be common in soil of the Experimental Farm of Fac. Agric., Minia Univ., Egypt.In pure liquid cultures, the immobilized cells exhibited much higher nitrogenase activity (about 57 fold) than the free ones. The encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In vitro biofilm studies have shown that bacterial exopolysaccharides can, in some but not all cases, provide protection against phage (2224); thus, we next examined whether P. aeruginosa exopolysaccharides protected aggregates from phage-mediated killing. P. aeruginosa PAO1 has the capacity to produce at least three extracellular polysaccharides; alginate, Pel, and Psl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro biofilm studies have shown that bacterial exopolysaccharides can, in some but not all cases, provide protection against phage (2224); thus, we next examined whether P. aeruginosa exopolysaccharides protected aggregates from phage-mediated killing. P. aeruginosa PAO1 has the capacity to produce at least three extracellular polysaccharides; alginate, Pel, and Psl.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in exopolysaccharide mutant biomass after treatment with phage indicates that the mechanism of aggregate tolerance is, at least in part, due to exopolysaccharide production. Exopolysaccharides have been shown to be important for phage tolerance in some, but not all, bacteria (2224), although these studies have not focused on aggregates. Another possibility is that the presence of Pel and Psl impacts the accessibility or level of the phage receptor.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that the cross-resistance observed was not as strong as the specific resistance evolved, the phages must be binding to the receptors in slightly different ways. Alternatively, phage-mediated selection might have led to both a general resistance mechanism (such as alginate production [37]) that confers resistance to allopatric phages and a more specific resistance (such as restriction modification or CRISPRrelated interference [34]) that confers resistance to the sympatric phage. The fact that we only observed fitness costs associated with resistance in multiple-phage environments is consistent with the accumulation of multiple costly resistance mutations, each conferring specific resistance to sympatric phages.…”
Section: Discussionmentioning
confidence: 99%
“…), production of extracellular compounds that can prevent phage access to host cells (Doolittle et al. ; Hammad ; Scanlan and Buckling ), or acquisition of novel CRISPR spacers targeting previously encountered phages (Barrangou et al. ), among other mechanisms (Labrie et al.…”
Section: Study Systemmentioning
confidence: 99%